2015
DOI: 10.3329/bjp.v10i2.22588
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol inhibits cadmium induced neuronal apoptosis by modulating calcium signalling pathway via regulation of MAPK/mTOR network

Abstract: <p>Cadmium, a toxic environmental contaminant, induces oxidative stress leading to various neurodegenerative disorders, where it interferes with homeos-tasis of intracellular free calcium ([Ca<sup>2+</sup>]i), leading to cellular damage and apoptosis. We investigated whether resveratrol, a plant-derived antioxidant could offer protection against cadmium-induced neuroapoptosis. Primary cortical neurons were exposed to cadmium (10 or 20 µM) with/without prior exposure to resveratrol (5, 10 or 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Trans ‐RES (3,5,4‐trihydroxy‐ trans ‐stilbene), a polyphenolic phytoalexin found in grapes, cranberries, and peanuts, is an excellent neuroprotective agent in both animals and humans . In various animal models of neurodegeneration, RES inhibited neural cell apoptosis and improved learning and memory function with many thanks to its antioxidant and ROS scavenging potentials and its ability to modulate numerous signaling pathways including Ca 2+ , ERK1/2, and JNK . Recently, we have shown that RES prevented tau hyperphosphorylation and memory deficits in cadmium chloride (CdCl 2 )‐induced rat's model of neurodegeneration by increasing GSH levels, inhibition of ROS, downregulation of Bax, and upregulation of Bcl‐2, mediated by activation of AMPK/PI3K/Akt axis activity .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trans ‐RES (3,5,4‐trihydroxy‐ trans ‐stilbene), a polyphenolic phytoalexin found in grapes, cranberries, and peanuts, is an excellent neuroprotective agent in both animals and humans . In various animal models of neurodegeneration, RES inhibited neural cell apoptosis and improved learning and memory function with many thanks to its antioxidant and ROS scavenging potentials and its ability to modulate numerous signaling pathways including Ca 2+ , ERK1/2, and JNK . Recently, we have shown that RES prevented tau hyperphosphorylation and memory deficits in cadmium chloride (CdCl 2 )‐induced rat's model of neurodegeneration by increasing GSH levels, inhibition of ROS, downregulation of Bax, and upregulation of Bcl‐2, mediated by activation of AMPK/PI3K/Akt axis activity .…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23][24] In various animal models of neurodegeneration, RES inhibited neural cell apoptosis and improved learning and memory function with many thanks to its antioxidant and ROS scavenging potentials and its ability to modulate numerous signaling pathways including Ca 2+ , ERK1/2, and JNK. [22][23][24][25] Recently, we have shown that RES prevented tau hyperphosphorylation and memory deficits in cadmium chloride (CdCl 2 )induced rat's model of neurodegeneration by increasing GSH levels, inhibition of ROS, downregulation of Bax, and upregulation of Bcl-2, mediated by activation of AMPK/PI3K/Akt axis activity. 26 Also, RES prevented neural apoptosis and preserved motor and memory function in rotenone-induced Parkinson's disease and postoperative cognitive dysfunction animal models by inhibition of ER stress and UPRrelated proteins.…”
mentioning
confidence: 99%
“…Administration of GSE normalized all these biomarkers (El‐Tarras, Attia, Soliman, Awady, & Amin, ). Lin, Peng, Yang, and Mi () exposed primary cortical neurons to Cd (10 and 20 μM) and RSV (5, 10, and 20 μM) for 12 hr. RSV caused noticeable decrease in neuronal apoptosis and caspase 3 induced by Cd.…”
Section: Chemical‐induced Toxicitymentioning
confidence: 99%
“…It also reduced ROS and Ca 2+ levels, along with regulation of alterations in MAPKinase pathway. Therefore, this could be a probable neuroprotective mechanism of RSV against Cd (Lin et al, ).…”
Section: Chemical‐induced Toxicitymentioning
confidence: 99%
“…The cells were incubated with floroquinone for 48 hours, fixed in ice-cold paraformaldehyde, rinsed in PBS and subsequently stained with 4,6-diamidino-2-phenylindole (DAPI) for 30 min at 37°C. A fluorescent microscope was used for the analysis of the nuclear fragmentation in DAPI-stained cells (Lin et al, 2015). TUNEL kit (Chemic on, USA) was used for performing TUNEL assay according to the manufacturer's instructions.…”
Section: Dapi Stainingmentioning
confidence: 99%